2016
DOI: 10.7904/2068-4738-vii(14)-5
|View full text |Cite
|
Sign up to set email alerts
|

NUTRITIVE VALUE OF FORAGE OF VETCH CULTIVARS (Vicia sativa L., Vicia villosa ROTH.)

Abstract: showed better forage quality of V. sativa compared to V. villosa. With the highest nutritive value was distinguished cultivars Liya, Vilena and Moldovskaya, which could be used as germplasm in future breeding programmes for quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The mean value of CP content was 192.2 g kg −1 . Similar results have been found for vetch grown in native pasture in Turkey [58] and for cultivated vetch in Bulgaria [23]. According to our results, vetch could exceed the requirements of small ruminants grazed in semi-arid regions for maintenance (9%), gestation (11%), and lactation (13%) [59][60][61].…”
Section: Nutritional Traitssupporting
confidence: 88%
See 2 more Smart Citations
“…The mean value of CP content was 192.2 g kg −1 . Similar results have been found for vetch grown in native pasture in Turkey [58] and for cultivated vetch in Bulgaria [23]. According to our results, vetch could exceed the requirements of small ruminants grazed in semi-arid regions for maintenance (9%), gestation (11%), and lactation (13%) [59][60][61].…”
Section: Nutritional Traitssupporting
confidence: 88%
“…These factors depend on the genotype of the plant and on its response to the environment in which it grows, i.e., on GXE interaction. The nutritive value of common vetch is generally high, and particularly, its protein content is higher compared with other annual legumes [23]. According to Abbeddou et al [2] the hay of common vetch is a valuable source of energy and protein for livestock in the dry areas of the Mediterranean basin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, seven vetch varieties were estimated under organic growing conditions. The results showed that the Moldavian variety Liya was distinguished by a higher ADGR (1.04 cm/day), greater PH (70.4 cm), and amount of AGB formed (by 55.0% above the average of the studied varieties) [33]. In another experiment conducted under organic conditions, five pea varieties were tested.…”
Section: Discussionmentioning
confidence: 97%
“…The common vetch plants have plasticity not only for adaptability to different soil and climate conditions, but it also has diverse use as grain, straw, hay, silage, and green manure along with soil improvement ability with nitrogen fixation [1][2][3]. Therefore, it is considered one of the most valuable protein and mineral resources for cattle and poultry in Turkey, Australia, New Zealand, China and Eastern Europe [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%